The Relationship Between First and Second Language Writing: Investigating the Effects of First Language Complexity on Second Language Complexity in Advanced Stages of Learning. Issue 3 (9th April 2020) - Ströbel, Marcus; Kerz, Elma; Wiechmann, Daniel
Abstract: Recent studies have uncovered substantial individual differences in first language (L1) language attainment across the lifespan and across multiple components of language. The existence of such variability raises the question of its role in second language (L2) learning. The existing body of research on L1–L2 relationships has primarily targeted reading comprehension by means of controlled experimental designs. This study extended existing research by investigating L1–L2 relationships in writing through the automatic analysis of linguistic complexity in paired samples of authentic production data. For each writing sample, a series of measurements of 12 indicators was obtained using a computational tool that implements a sliding‐window approach. Results from mixed‐effects modeling revealed significant relationships between L1 complexity and L2 complexity for all but one measure, indicating that an L1 effect is robust across different levels of linguistic description. Abstract :